Looking for trustworthy answers? Westonci.ca is the ultimate Q&A platform where experts share their knowledge on various topics. Get immediate and reliable answers to your questions from a community of experienced experts on our platform. Get detailed and accurate answers to your questions from a dedicated community of experts on our Q&A platform.

please answer as soon as possible, and show work

Please Answer As Soon As Possible And Show Work class=

Sagot :

Answer:

6

Step-by-step explanation:

Your intervals are x=-2, and x=0. In this case, x=-2 will be a, and x=0 will be b.

To find the average rate of change, you have to first find f(-2) and f(0)

[tex]f(-2)=1-3(-2)^2\\f(-2)=1-3(4)\\f(-2)=-11\\[/tex]

Then, f(0)

[tex]f(0)= 1-3(0)^2\\f(0) = 1-3(0)\\f(0) = 1[/tex]

Now you know f(-2) is -11, and f(0) is 1.

Next, you plug these into the average rate of change formula, which is

[tex]\frac{f(b)-f(a)}{b-a}[/tex]

Flug in -11 and 1 on the numerator, and -2 and 0 on the denominator.

[tex]Average = \frac{(1)-(-11)}{(0)-(-2)} \\\\[/tex]

[tex]Average =\frac{12}{2} \\Average = 6[/tex]